Resilience factors in nursing workers in the hospital context - Silva, Silmar Maria da; Baptista, Patricia Campos Pavan; Silva, Fábio José da; Almeida, Mirian Cristina dos Santos; Soares, Rosimeire Angela de Queiroz (Revista da Escola de Enfermagem da USP, 2020)
Objective: To investigate the level and factors related to resilience in nursing workers in the hospital context. Method: A cross-sectional study conducted with nursing workers of a university hospital in the city of São Paulo. Data were collected through a questionnaire containing sociodemographic and labor variables and the Resilience Scale. Results: It was found that 45.3% of the 375 nursing workers investigated had a moderately low/moderate level of resilience, followed by a moderately high/high level (39.5%), and then a low level of resilience (15.2%). Age, working time in the institution, and working time in the profession showed a statistically significant correlation with resilience. The model showed that there is an increase of 0.289 points on the Resilience Scale for each year of age, regardless of the other variables. Conclusion: The resilience level of nursing workers is moderate to high. Age was determinant in resilience, as well as working time in the profession and institution.